Resignifying the compulsory notification process from the perspective of Permanent Health Education: An experience report (Research, Society and Development, 2021)
The Permanent Education in Health policy (EPS) presents challenges and strategies for the improvement of health care quality. Through it, knowledge and experiences will be a common good to all, according to the perspective of the National Policy for Permanent Education in Health (PNEPS). In light of this, it is necessary to give a new meaning to the compulsory notification process, in order to contribute to the promotion, prevention and control of diseases, grievances and public health events. We believe that EPS is the strategy capable of providing health care professionals with the understanding of the significance and relevance that this field of knowledge needs. In this context, this study aims to present the experience report on the EPS challenges faced in the construction of the Educational Technological Product regarding compulsory notification. The results show that the Educational Technological Product, in line with the PNEPS goals, as a teaching-learning strategy through video lessons to achieve the reframing of the process of compulsory notifications by health care professionals, is an effective means of contributing to the reconstruction of the knowledge, attitudes and practices in the context of Epidemiological Surveillance. Although countless bibliographic references mention the relevance of EPS regarding underreporting and improving the data quality in Compulsory Notification Sheets, no studies were identified discussing strategies to overcome this problem in a practical and applicable way.